Sugar cane extracts as natural taste modulators: potential for sugar reduction in beverages and beyond - Llalla Vidal, Thalia Marina; Macnab, Gregor; Mitchell, Shane; Flavel, Matthew (Frontiers in Nutrition, 2025)
The reduction of added sugars in food and beverage products has become a global health priority, driven by rising rates of obesity, diabetes, and cardiovascular disease. Yet, achieving sugar reduction without compromising taste remains a major challenge for manufacturers. This review explores the potential of sugar cane extracts—specifically Modulex™, as natural taste modulators capable of enhancing sweetness, masking bitterness, and improving mouthfeel in reduced-sugar formulations. Derived from Saccharum officinarum, these extracts contain a complex mixture of sugars, polyphenols, amino acids, and minerals that act through multimodal sensory pathways, including interactions with sweet (T1R2/T1R3) and bitter (TAS2R) taste receptors. Evidence from sensory studies demonstrates that sugar cane extracts can significantly improve the flavor profile and consumer acceptability of beverages sweetened with natural or artificial low-calorie sweeteners. This review discusses the biochemical basis of these effects, their regulatory positioning, and their implications for product development aligned with clean-label trends and public health goals. Sugar cane extracts represent a promising ingredient for next-generation sugar reduction strategies that balance health, taste, and consumer preference.